Implementation Of Collective Dzikir In Forming The Religious Character Of Students Through The Naqsyabandiyah Mudzhariyah Thariqah - Aisyatul Farhah; M. Yunus Abu Bakar (Ibn Khaldun University, Bogor, 2025)
In the current millennial era, it is a very important task for an educator in the formation of the religious character of students. Not only to add positive activities for students, but also to strengthen the foundation of faith that will continue to be held firmly in the students. This study was conducted with the aim of examining the implementation of collective dhikr in the formation of the religious character of students through Thariqah Naqsyabandiyah Mudzhariyah. The research method used in this study is library research, namely by collecting various data from books, journals, and other scientific sources relevant to the theme of dhikr, the formation of religious character, and the teachings of Thariqah Naqsyabandiyah Mudzhariyah. In this study aims to be able to provide research results that show that Collective Dhikr activities have a very important role in fostering religious values ​​​​to educators. Such as discipline of worship, patience, sincerity, and togetherness. Through the continuous implementation of this dhikr, students can not only form a spiritual closeness with God, but can also build a strong moral and social character according to the teachings of Sufism. Keywords: Collective Dhik; Religious Character; Naqsyabandiyah Mudzhariyah Islamic Boarding School; Sufism Education;